(untitled) (International journal of medical sciences, 2026)
Pertussis, caused by Bordetella pertussis, remains a significant public health concern despite widespread vaccination. Antibiotic therapy plays a crucial role in eradicating bacterial carriage, reducing transmission, and mitigating disease severity when administered early. The present review analyzes the pharmacokinetic (PK) and pharmacodynamic (PD) characteristics of antibiotics recommended for pertussis treatment, including macrolides (azithromycin, clarithromycin, erythromycin) and trimethoprim-sulfamethoxazole (TMP-SMX). Data were synthesized from peer-reviewed publications, clinical guidelines, and pharmacological references. Macrolides demonstrate high intracellular penetration, prolonged half-lives (notably azithromycin), and concentration-dependent activity against B. pertussis. TMP-SMX exhibits time-dependent bacteriostatic effects by sequential inhibition of folate synthesis. Understanding PK/PD parameters such as minimum inhibitory concentration (MIC), area under the concentration–time curve (AUC), peak plasma concentration (Cmax), and time above MIC (T>MIC) is essential for optimizing dosing regimens and minimizing resistance.